2022
DOI: 10.3390/ijerph19159122
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Patients with Prostate Cancer, at Cancer Diagnosis and after a One-Year Follow-Up

Abstract: Prostate cancer (PCa) is the most prevalent among men, and psychological symptoms may affect many patients. This study aims to describe the prevalence of probable anxiety and depression before PCa treatments and after one year and to identify sociodemographic and clinical factors associated with these outcomes. Between February 2018 and March 2020, 292 patients recently diagnosed with PCa were recruited at the Instituto Português de Oncologia—Porto. The Hospital Anxiety and Depression Scale (HADS) was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…37,38 One previous study of PCa survivors found that poorer overall physical health was associated with older age and more comorbidities, whereas poorer mental health was associated with younger age, more comorbidity, and higher stage at diagnosis. 39 Our study identifies subgroups of PCa survivors who may be at risk for poor overall health during their survivorship.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…37,38 One previous study of PCa survivors found that poorer overall physical health was associated with older age and more comorbidities, whereas poorer mental health was associated with younger age, more comorbidity, and higher stage at diagnosis. 39 Our study identifies subgroups of PCa survivors who may be at risk for poor overall health during their survivorship.…”
Section: Discussionmentioning
confidence: 94%
“…We also observed a strong association of having comorbidities with being in the low HRQOL profile, consistent with previous studies of PCa showing that greater comorbidity burden is associated with worse HRQOL. 39,51,52 Men who received systemic therapy (mostly hormonal therapy) were more likely to be in the low HRQOL profile than men who did not receive therapy, adjusting for stage and all other variables, which may relate to hormonal therapy increasing fatigue and affecting general physical function. 53…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis and treatment of PCa cause not only physical complications, such as urinary incontinence, urinary tract irritation, and erectile dysfunction [ 2 ], but also mental health issues. Anxiety is the most frequently reported negative emotion among patients with PCa, with incidence rates ranging from 15.09 to 32.6%, as revealed by various studies employing different anxiety assessment tools [ 3 , 4 ]. In patients with PCa, regular testing of the prostate-specific antigen (PSA) index is essential to monitor treatment outcomes and disease progression [ 5 ].…”
Section: Introductionmentioning
confidence: 99%